Bazedoxifene for the treatment of osteoporosis. (3rd July 2019) - Yavropoulou, Maria P.; Makras, Polyzois; Anastasilakis, Athanasios D.
ABSTRACT: Introduction : Bazedoxifene (BZD) is a third-generation selective estrogen receptor modulator approved for the treatment of postmenopausal osteoporosis with additional favorable effects in lipids, uterine and breast tissue. Areas covered : In this review, the authors outline clinical data regarding the efficacy, safety, and tolerability of continuous BZD administration up to seven years in randomized, placebo-controlled, phase III clinical trials. Long-term treatment with BZD for postmenopausal osteoporosis is generally safe and well tolerated. BZD achieves small but significant increases in the bone mineral density of the lumbar spine but not the total hip. In addition, BZD reduces significantly the risk of vertebral fractures but not of non-vertebral and hip fractures, with the exception of high fracture risk postmenopausal women in whom BZD significantly reduces non-vertebral fractures. Expert opinion : BZD does not seem to offer significant advantages over the other available antiresorptive agents. However, considering the need for long-term management of osteoporosis, BZD may have a place in the long-term therapeutic planning of the disease.